2020
DOI: 10.3390/toxins12060422
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Potential for Cross-Interactions of Antitoxins in Type II TA Systems

Abstract: The diversity of Type-II toxin–antitoxin (TA) systems in bacterial genomes requires tightly controlled interaction specificity to ensure protection of the cell, and potentially to limit cross-talk between toxin–antitoxin pairs of the same family of TA systems. Further, there is a redundant use of toxin folds for different cellular targets and complexation with different classes of antitoxins, increasing the apparent requirement for the insulation of interactions. The presence of Type II TA systems has remained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 226 publications
(374 reference statements)
0
15
0
1
Order By: Relevance
“…In contrast, it was shown that the higA mutant exhibits reversed phenotype with decreased biofilm formation, elevation in PDEs expression, and reduced c-di-GMP levels ( 22 , 41 ). The contrasting results are probably attributable to the fact that prrT/A is a combined system in which the antitoxin mutant effect is mainly due to the upregulation of the toxin, as the ParE toxin was shown to enhance biofilm formation in E. coli ( 37 ) significantly.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In contrast, it was shown that the higA mutant exhibits reversed phenotype with decreased biofilm formation, elevation in PDEs expression, and reduced c-di-GMP levels ( 22 , 41 ). The contrasting results are probably attributable to the fact that prrT/A is a combined system in which the antitoxin mutant effect is mainly due to the upregulation of the toxin, as the ParE toxin was shown to enhance biofilm formation in E. coli ( 37 ) significantly.…”
Section: Discussionmentioning
confidence: 98%
“…It can only occur if some cross-regulation between other chromosomal TA systems has occurred. An interaction between noncognate complexes of toxins and antitoxins, which can bind to other TA promoter regions and regulate the expression, has been reported ( 36 38 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This work contributes to the understanding of TA interfaces and it offers a structure-based explanation for non-cognate toxin-antitoxin interactions [8]. Tu et al revised the concept that a toxin paralogue may provide a "cure" against the acquisition of highly similar TA systems, such as those found on plasmids or invading genetic elements that frequently carry virulence and resistance genes [9]. Only limited cross-reactions have been observed between chromosomal and mobile genetic elements systems, perhaps due to bias in the type of experiments and functions of TA systems pursued.…”
mentioning
confidence: 99%
“…No primeiro grupo a antitoxina é uma RNAse que degrada o mRNA da toxina. O sistema GhoS-GhoT é um representante do grupo V (WEN;BEHIELS;DEVREESE, 2014;MASUDA et al, 2012;WANG et al, 2012) presentes em cromossomos e 13 presentes em plasmídeos (TU et al, 2020).…”
Section: Classificação Dos Sistemas Taunclassified